Pengaruh Halal Awareness dan Kualitas Produk Terhadap Keputusan Pembelian Produk Korean Food Pada Generasi Z di Kota Pekanbaru - Assifa Fajrina; Nurrahmi Hayani (Pelantar Press, 2023)
This study aims to determine the effect of Halal Awareness and Product Quality on purchasing decisions for Korean Food Products in Generation Z in Pekanbaru City. The number of samples in this study was 100 respondents using the purposive sampling method and using the lamb show formula with the criteria that generation z has bought or is currently buying Korean food products. The method in this study is quantitative with multiple linear regression and uses the SPSS version 29 program. The results of this study using the T-test variable Halal Awareness and Product Quality partially have a significant effect on Purchasing Decisions. By using the F Test the variable Halal Awareness and Product Quality simultaneously have a significant effect on Purchasing Decisions. The coefficient of determination (R2) with a value of 0.517 or 51.7% indicates that purchasing decisions are simultaneously influenced by Halal Awareness and Product Quality by 51.7%, while the remaining 48.3% is influenced by other variables not used in this study.